ANALISIS PENGARUH FAKTOR INTERNAL DAN FAKTOR EKSTERNAL TERHADAP STABILITAS BANK UMUM SYARIAH DI INDONESIA PADA SEBELUM DAN SAAT PANDEMI COVID – 19 - Febriana, Eliza; Hadiani, Fatmi (Accounting Department, Politeknik Negeri Bandung, 2024)
Abstract: This research compares the stability of Sharia Commercial Banks before and during the COVID-19 pandemic, by looking at the impact of internal and external factors. 10 banks that met the criteria were included in the purposive sample used to select the sample for this research. The data obtained comes from the World Bank, Central Statistics Agency, and the official website of each Sharia Commercial Bank. This research includes internal variables such as CAR, NPF, and ISR and external factors consisting of inflation, GDP growth, and bank competition. As an analysis tool, Stata software is used to perform panel data regression and t-test data analysis. Based on the tests that have been carried out, the best model chosen is FEM with CAR, ISR and competition results having a significant positive influence, NPF and Inflation having an insignificant negative influence and GDP growth having an insignificant positive influence. The Wilcoxon Signed Rank Test was used because the research data was not normally distributed. As a result, the stability of Sharia Commercial Banks before and during the COVID-19 pandemic was no different. Keywords: Stability, Capital Adequacy Ratio, Non-Performing Financing, Islamic Social Responsibility, Inflation, GDP Growth, Bank Competition.